PENGARUH PENERAPAN PEMBELAJARAN AKTIF TIPE EVERYONE IS A TEACHER HERE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 3 SAWAHLUNTO - Purnama, Ridho Hadi (Pendidikan Matematika, 2014)
The background of the research is the lack of studentâs Math concept. Theresearch aims to know how the development of studentâs Math conceptunderstanding of VIII grade students of Public Junior High School (SMPN) 3Sawahlunto through quiz and the application influence of active Learning Modelof ETH type to the studentâs Math concept understanding in Public Junior HighSchool (SMPN) 3 Sawahlunto. The type of the research is pre experimentresearch with the research design of one shot case study. The population of theresearch is the VIII grade students consisting of seven classes. The research usesa random sampling technique. The selected sampling class is VIII.1 class. Theinstruments used on the research are essay quiz and post-test with the reliabilitytest is 0.755. The technique of analyzing the data is descriptive analysis. Based onthe post-test result of the sampling class students, it is found that the average ofsampling class is 72.6. It is higher than a Minimum Completeness Criteria (KKM)i.e. 70. Based on the quiz result, it is also found that there is an increase ofstudentâs grade average. It can be concluded that the using the active LearningModel of ETH type gives influence to the studentâs Math concept understanding inPublic Junior High School (SMPN) 3 Sawahlunto.